PENGELOLAAN ZAKAT, INFAK DAN SEDEKAH DALAM PENGEMBANGAN USAHA MIKRO (Studi Kasus Pada Badan Amil Zakat Nasional Kabupaten Tulungagung) - Saifudin, Ahmad (LIPI, 2019)
The purpose of this research is to know the management of Zakat, Infaq, and charity in the development of micro-business case studies on the Badan Amil Zakat Nasional (BAZNAS) of Tulungagung District. The method Adapaun used in the study is a descriptive field method with a qualitative approach. Data collection techniques using interviews, participant observation, and documentation studies. Data checking is done using trianggulation techniques, discussions with peers. While checking the audience of research data by the Supervisor lecturer as an auditor. The results showed that the management of ZIS funds in BAZNAS in Tulungagung district has a way to manage the funds. So that the funds can run smoothly, effectively and efficiently then in need of management. In planning gathering BAZNAS Tulungagung has certain points to be aware of. These Adapaun points are; Organisations should know the circumstances of the environment in which the organization is located, then the object gathering us to the segments of who, whether individuals, corporations or foundations, after all is done then the institution or organization makes a strategy and Tactics to be used in gathering to achieve a predetermined target. In order to realize BAZNAS in the honest, fair and trustworthy district, the process of transportation and accountability is sought as much as possible to realize the trust of Muzakki.